Pengaruh Blended Learning Terhadap Proses Dan Hasil Belajar Siswa Pada Mata Pelajaran Fiqih Di MTsN 12 Majalengka - UFN Maesaroh (Oasis : Jurnal Ilmiah Kajian Islam, 2020)
This study aims to explain how much influence the method of blended learning in Fiqh lessons on the process and student learning outcomes in the 12th Majalengka State Islamic Senior High School Madrasa. By using the quasi-experimental method. The design used was Pretest-Posttest Non Equivalent Control Group Design, with a population sample of 25 students from grade VII in Madrasah Tsanawiyah Negeri (12) Majalengka. The results obtained are (1) The learning process of the Fiqh of students taught using blended learning models and those not taught with blended learning models there are significant differences. (2) The learning process of jurisprudence in students not taught with the blended learning model is in the medium categorization. While the learning process of jurisprudence for students who use the blended learning model is in a high categorization. (3) Blended learning affects the class VII learning process and learning outcomes. Cognitive, affective and psychomotor learning outcomes in the experimental class increased by 26.44%, while the control class was 19.84%.Penelitian ini bertujuan untuk menjelaskan seberapa besar pengaruh metode Blended Learning dalam pembelajaran Fiqih terhadap proses dan hasil belajar siswa di Madrasah Tsnawiyah Negeri 12 Majalengka.Â  Dengan mengunakan metode eksperimen semu. Desain yang digunakan adalah â€œPretest-Posttest Non Equivalen Control Group Desainâ€, dengan sampel populasi sebanyak 25 siswa dari kelas VII di Madrasah Tsanawiyah Negeri (12) Majalengka. Hasil penelitian yang diperoleh adalah (1) Proses belajar Fiqih peserta didik yang diajarkanÂ  dengan menggunakan model pembelajaran blended learning dan yang tidak diajar dengan model pembelajaran blended learning terdapat perbedaan yang cukup signifikan. (2) Proses belajar Fiqih pada peserta didik yang tidak diajar dengan model pembelajaran blended learning berada pada kategorisasi sedang. Sementara proses belajar Fiqih pada peserta didik yang menggunakan model pembelajaran blended learning berada pada kategorisasi tinggi. (3) Pembelajaran blended learning berpengaruh terhadap proses dan hasil belajar siswa kelas VII. Hasil belajar kognitif, afektif dan psikomotor pada kelas eksperimen mengalami peningkatan sebesar 26,44%, sedangkan kelas control sebesar 19,84%.